2021
DOI: 10.1515/sjpain-2021-0050
|View full text |Cite
|
Sign up to set email alerts
|

Disability, burden, and symptoms related to sensitization in migraine patients associate with headache frequency

Abstract: Objectives This observational study aimed to assess the difference in disability, burden, and sensitization between migraine patients with low-frequency headache attack (1–8 headache days/month), high-frequency headache attack (9–14 headache days/months), and patients with chronic migraine (>14 headache days/months). Methods Migraine patients with or without aura were divided into three groups according to headache frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…In a study consisting of 136 patients with migraine, compared with patients with low-frequency EM (1–8 headache days a month), patients with high-frequency EM (9–14 headache days a month) and CM (>14 headache days a month) had similar severe degrees of headache-related disability and CS-related symptoms. 44 A comparison of migraine patients with 15 or more headaches per month and those with 8 to 14 or more headache days per month showed no differences in parameters such as depression, anxiety, and pain scores between the two groups. 45 Becerra et al 46 investigated differences in brain metabolite in the anterior cingulate cortex during the interictal phase in EM patients using magnetic resonance spectroscopy, and concluded that the brain in EM patients is hyperexcitable during the interictal state based on the findings of alterations of metabolites, such as aspartate /Cre, N-acetyl aspartate /Cre and glutamine /Cre.…”
Section: Methodsmentioning
confidence: 89%
“…In a study consisting of 136 patients with migraine, compared with patients with low-frequency EM (1–8 headache days a month), patients with high-frequency EM (9–14 headache days a month) and CM (>14 headache days a month) had similar severe degrees of headache-related disability and CS-related symptoms. 44 A comparison of migraine patients with 15 or more headaches per month and those with 8 to 14 or more headache days per month showed no differences in parameters such as depression, anxiety, and pain scores between the two groups. 45 Becerra et al 46 investigated differences in brain metabolite in the anterior cingulate cortex during the interictal phase in EM patients using magnetic resonance spectroscopy, and concluded that the brain in EM patients is hyperexcitable during the interictal state based on the findings of alterations of metabolites, such as aspartate /Cre, N-acetyl aspartate /Cre and glutamine /Cre.…”
Section: Methodsmentioning
confidence: 89%
“…The higher the score, the higher the disability. 32,33 Details of the assessment procedure are reported in the Supporting Information (Appendix S1).…”
Section: Headache Disability Index (Hdi)mentioning
confidence: 99%
“…These data were widely available in the medical records and headache frequency is a well-established measure of the disability associated with migraine. [23][24][25] CD phenomenology was assessed by descriptions charted by movement specialists and severity was assessed with the Toronto Western Spasmodic Torticollis Rating Scale (TWSTRS). The TWSTRS score is a well-established metric to quantify dystonia and has high inter-rater reliability.…”
Section: Measurementsmentioning
confidence: 99%
“…Another limitation is the use of migraine frequency as a proxy for headache improvement after BoTNA treatment. Although it is a valid marker, [23][24][25] future studies should include measures of headache severity, disability, and impact on quality of life. Additionally, our movement specialist did not routinely use EMG guidance for toxin delivery due to the low pain tolerance of the patients.…”
Section: Con Clus Ionmentioning
confidence: 99%